UTANG DALAM SEWA MENYEWA SEBAGAI DASAR PERMOHONAN PENUNDAAN KEWAJIBAN PEBAYARAN UTANG (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR:59/Pdt.Sus/PKPU/2014/PN.Niaga.Jkt.Pst Jo. - IDRIS SARDI SEMBIRING (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Sunarmi2. Hasim Purba3. Dedi Harianto A leasing contract comes from the relationship between PKPU petitioner and PKPU petitionee. In settling the debtor’s debt which has fallen due, the judge refers to Law No. 37/2004 on Bankruptcy; he, therefore, accepts the request for PKPU within 30 days commencing from the Verdict is handed down. The debt in leasing contract becomes the reason of requesting for filing bankruptcy with the principle of business continuity in helping pay off the debt between PKPU petitioner and PKPU petitionee. By debt restructuring, debtor’s debt will be paid off. Even though the leasing down-payment has been paid, leasing contract cannot be stopped before the period of leasing ends. A creditor, who thinks that the debtor will not be able to pay off when it falls due, will give an opportunity to the debtor to pay off the debt and reorganize his company based on good faith. Keywords: Debt, PKPU, Leasing